2019
DOI: 10.1016/j.eclinm.2019.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Surgical duration is associated with an increased risk of periprosthetic infection following total knee arthroplasty: A population-based retrospective cohort study

Abstract: BackgroundTotal knee arthroplasty (TKA) is one the most common elective procedures in the world. Post-operative infection is one of its most devastating complications, often necessitating multiple additional surgeries. We aimed to describe the relationship between surgical duration and risk of deep infection following primary elective TKA.MethodsIn this cohort study we analyses primary TKAs done between 2009 and 2016 in Ontario, Canada. We utilized restricted cubic splines to identify a threshold of surgical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 22 publications
2
45
2
Order By: Relevance
“…Orthopaedic oncologists are therefore required to evaluate possible risk factors for failure and, ideally, identify areas of optimization potential. The length of surgery as a potential risk factor has been studied previously [ 20 ]; however, previous results have been inconclusive [ 13 , 14 , 15 ]. As sarcoma resection and megaprosthetic reconstructions have a longer surgical duration and are associated with a higher risk of failure compared to non-oncological arthroplasty procedures [ 18 , 21 ], modifying a procedure related risk factor, such as the duration of the surgery, would offer surgeons a chance to reduce the burden of megaprosthetic revision.…”
Section: Discussionmentioning
confidence: 99%
“…Orthopaedic oncologists are therefore required to evaluate possible risk factors for failure and, ideally, identify areas of optimization potential. The length of surgery as a potential risk factor has been studied previously [ 20 ]; however, previous results have been inconclusive [ 13 , 14 , 15 ]. As sarcoma resection and megaprosthetic reconstructions have a longer surgical duration and are associated with a higher risk of failure compared to non-oncological arthroplasty procedures [ 18 , 21 ], modifying a procedure related risk factor, such as the duration of the surgery, would offer surgeons a chance to reduce the burden of megaprosthetic revision.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the retrospective analysis of more than 92.000 patients undergoing TKA in the Ontario region of Canada between 2009 and 2016 Ravi et al recently found a statistically significant relation between procedure lengths and the number of deep infections. 25 They observed that patients with a "long" surgical duration (≥100 min) suffered from a higher rate of PJI within a year of their surgery than patients with a "short" duration (1.1% versus 0.6%). Similar results were also obtained by Garbarino et al 24 who observed higher PJI rates in cases >121 minutes duration of surgery (1.4%) compared to those <85 minutes (0.3%).…”
Section: Procedure-specific Risk Factorsmentioning
confidence: 98%
“… 69 The failure and abandonment of ROBODOC mid-procedure meant surgical times in theatre were protracted, reducing theatre time utilization and increasing concerns of infection. 69 , 79 , 80 These potential extra costs and lack of superior survivorship data combined with the initial upfront and running costs of approximately $545,000 and $1,360 respectively, failed to prove robotic TKA was cost-effective. 81 …”
Section: Clinical Applicationmentioning
confidence: 99%